Relationship Between Body Mass Index and Physical Activity with the Incidence of Osteoarthritis in Patients Over 40 Years of Age - Hendrik Kurniawan; Anna Maria Dewajanti; Runi Asmarani; Manda Setyo Wulandari (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Osteoarthritis is a chronic degenerative disease, the disease is often experienced by the elderly. In 2013 the prevalence of osteoarthritis in Jakarta in accordance with the doctor's diagnosis or health workers is 8.9% and that in accordance with the doctor's diagnosis or health and in accordance with the symptoms was 21.8%. This disease occurs as a result of a combination between the degradation of cartilage, bone remodeling, and inflammatory joint fluid Many factors can affect this disease are elderly, overweight, strenuous physical activity, trauma and many things lainnya. Responden in this study were taken as many as 72 people and 44.4% of them suffer from osteoarthritis caused by obesity, excessive physical activity or old age. In this study using purposive sampling method in data retrieval, then entered and processed using a computer program, the program SPSS (Statistical Package for Social Science) with Chi-square test and Mann-Whitney. Dependent variable used in this research was the respondents who were diagnosed with osteoarthritis or have other joint disease, while independent variables used were age, physical activity and body mass index (BMI). From the data processing showed that age and physical aktvitas have a significant relationship with osteoarthritis. While the body mass index (BMI) has no connection due to too many respondents who are obese. But obesity itself is one of the factors that can lead to osteoarthritis.